PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL ROPES PADA MATERI TEKANAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP - Panjaitan, Ratih Monika Sales; Nor, M; Azizahwati, Azizahwati (LPPM UNIVERSITAS PGRI SILAMPARI, 2023)
This study aims to design learning tools based on the ROPES model on the subject of Pressure to Improve Learning Outcomes of Class VIII SMP students and to produce learning tools based on the Ropes model on the material Pressure to Improve Learning Outcomes of Class VIII SMP students. This research was conducted at the Physics Education Laboratory, FKIP, University of Riau. The subject of this study was a physics learning tool based on the ROPES model which was developed including the Learning Implementation Plan (RPP), Student Worksheets (LKPD), and learning achievement tests on pressure material for class VIII SMP. In addition, the test subjects involved in this development research consisted of material experts, namely validators or teams/experts or physics education lecturers who validated ROPES-based science learning tools. The development model used in this study is Research and Development (R&D), with a 4D model. Based on the results of the research data, it was concluded that the learning device using the ROPES model in the pressure material for class VIII SMP was declared valid with an overall average score of 3.43 and was stated to be very valid and feasible to use as a learning tool that helps teachers and students improve student learning outcomes class VIII junior high school students on pressure material and can be used as teaching material in the learning process at school.